Exploring Factors Affecting Research Engagement of Instructors in Davao de Oro State College: Bases for Enhancement and Policy Recommendations - Rebucas, Rey John B.; Sangco, Loren; Cubio, Chrizon Rian; Evardo Jr., Orville J. (Future Science / FSH-PH Publications, 2025)
Research engagement in Philippine Higher Education Institutions (HEIs) is a pressing challenge. Despite its recognized importance for instructional innovations and institutional development, many faculty members avoid research, even when incentives are available. This qualitative-transcendental phenomenology explores and describes the experiences and insights of instructors on the factors affecting their research engagement. Through purposive sampling, specifically the criterion sampling technique, thirty-two (32) participants were selected from the four branches of Davao de Oro State College (DdOSC). The validated interview guide questions were used as the primary instrument in obtaining data through in-depth interviews and focus-group discussion, and the responses were thoroughly analyzed using thematic analysis. The significant factors identified by faculty were graduate studies and work responsibilities. Additionally, their lack of technical research writing knowledge contributed to their research limitations. Faculty members emphasized the need for ongoing research guidance, mentorship, and a wider range of incentives, such as integrating research into teaching loads, salary increases, and travel opportunities. Communication gaps between faculty and institutional research policies were evident, as some faculty members were unaware of the college's support. This study's implications stress the need for institutions to reconsider faculty workloads, offer additional training, and establish support systems that create a more research-friendly environment. Addressing these factors and expanding incentives can inspire faculty to participate in research activities, fostering a vibrant research culture and advancing knowledge within the academic community.